Cultural Diplomacy: César Vallejo Evening at IWL RAS - Victoria Yu. Popova (Литература двух Америк)
The article provides an overview of the Panel Discussion dedicated to the Peruvian poet César Vallejo, which was co-organized by the Embassy of Peru and the A.M. Gorky Institute of World Literature of the Russian Academy of Sciences on October 21, 2024 in the IWL RAS. The guest of honor of the Institute of World Literature was Ambassador Extraordinary and Plenipotentiary of the Republic of Peru to the Russian Federation Juan Genaro Del Campo Rodríguez, whose report opened the panel. The discussion brought together Russian and foreign researchers from the Embassy of Peru, the IWL RAS, Autonomous University of Madrid, and the University of Manchester. The papers covered various aspects of César Vallejo’s life and work: biographical details, analysis of his poetry and prose, his Soviet contacts, three visits to the USSR, Russian travelogues, interaction with Vladimir Mayakovsky, correspondence with F.V. Kelin, etc. The discussion became a notable event in Russian academic life, gathering about a hundred listeners and, undoubtedly, made a significant contribution to the study of César Vallejo work, to the history of the 20th century Peruvian literature, Soviet-Peruvian and Soviet- Latin American literary connections.